Penentuan Jumlah Forklift Dalam Pelayanan Peti Kemas Di PT Tempuran Mas Ambon - N. E. Maitimu (ARIKA, 2012)
PT Tempuran Mas is a company engaged in the service pack fairies. The company is based in Jakarta and Ambon is one of the branches. PT Tempuran Mas Ambon already have enough customers so that they also use the services of quite a lot. The purpose of this study was to determine the number of forklift needs in the process of unloading containers at the stacking of containers, so as to move containers quickly and safely to reduce the operation time. Workload for each day in a row is 40.33; 89.98: 20.94: 86.8: 66.74: 85.54, and 51.55 minutes / hour. This value indicates that the forklift business days 2, 4, 5, and 6 have large workloads that need attention to avoid poor performance in the removal of container stacking containers. Of research results and calculations show that the number of forklifts to be obtained every working day is different and not in accordance with the conditions existing in the company .. F-1 working day, weekdays F-3 and F-7 working days requires a forklift unit, while the F-2 work days, days kerja4 F-, F-5 working days, working days and the F-6 requires two units of forklifts . So that the necessary addition of 1 unit forklift again.